Molecular Mechanisms of Autophagy Regulation in Plants and Their Applications in Agriculture - Cao, Jia-Jian; Liu, Chen-Xu; Shao, Shu-Jun; Zhou, Jie (Frontiers in Plant Science, 2021)
Autophagy is a highly conserved cellular process for the degradation and recycling of unnecessary cytoplasmic components in eukaryotes. Various studies have shown that autophagy plays a crucial role in plant growth, productivity, and survival. The extensive functions of plant autophagy have been revealed in numerous frontier studies, particularly those regarding growth adjustment, stress tolerance, the identification of related genes, and the involvement of metabolic pathways. However, elucidation of the molecular regulation of plant autophagy, particularly the upstream signaling elements, is still lagging. In this review, we summarize recent progress in research on the molecular mechanisms of autophagy regulation, including the roles of protein kinases, phytohormones, second messengers, and transcriptional and epigenetic control, as well as the relationship between autophagy and the 26S proteasome in model plants and crop species. We also discuss future research directions for the potential application of autophagy in agriculture.